Comparison of Ushul Al-Hukm With Western Legal Theory - Latif, Muhammad Sabri; Hanafi, Yusuf; Hadi, Rizal; Zulhelmi, Zulhelmi; Ilyas, Ahmad Ghufran (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
This article is the result of a review of the book "Al-Islam Wa Ushul Al-Hukm" by 'Ali Abd al-Raziq, which offers an in-depth analysis of the relationship between politics and religion, especially regarding the concept of the caliphate in Islam. 'Ali Abd al-Raziq argues that the caliphate is not mandatory in Islam and that Islamic law can be interpreted flexibly according to the context of time and place, without being tied to the traditional caliphate system. This book highlights al-Raziq's view that the Prophet Muhammad was more of a spiritual leader than a head of state in the modern sense, so that Muslims were free to choose a form of government that suited their social and political needs, including a model that separated religion from state affairs. This view approaches the principle of secularism in Western legal theory, which advocates a separation between religious and state institutions. Although al-Raziq's views were controversial, especially among traditional ulama, he opened a new discourse about flexibility in the application of Islamic principles in modern governance. The book emphasizes that the primary goals of government are social justice and the welfare of the people, values ??that are in line with Western legal theory. This view shows that although the methods and sources of law are different, these two approaches both try to achieve a just and prosperous society.